PENGARUH PUPUK ORGANIK CAIR GAMAL DAN UREA TERHADAP PERTUMBUHAN VEGETATIF BIBIT KAKAO (Theobroma cacao. L): EFFECT OF LIQUID ORGANIC FERTILIZER GAMAL AND UREA ON VEGETATIVE GROWTH OF COCOA SEEDS (Theobroma cacao. L) - Mahdalena; Tutik Nugrahini; Frederich Febrian Hermanda (Universitas Widya Gama Mahakam, 2021)
Research the effect of liquid organic fertilizer gamal and urea on vegetative growth of cocoa seeds (Theobroma cacao. L). The study was conducted for 12 weeks (3 months) from July 2021 - October 2021. The research was carried out in the Agrotechnology Experimental Garden at Widya Gama Mahakam University Samarinda. Research uses The research method used a Randomized Block Design (RAK) with a 4 x 4 factorial experiment consisting of 3 replications. The first factor is Urea Fertilizer (U) which consists of 4 levels, namely U0 (control), U1 (3 g/polybag), U2 (6 g/polybag), U3 (9 g/polybag). The second factor was Gamal Leaf POC (G) which consisted of 4 levels, namely G0 (control), G1 (200 ml/polybag), G2 (250 ml/polybag), G3 (300 ml/polybag). The expected output is to provide information about the best dose of Urea fertilizer for the vegetative growth of cocoa seedlings for the community. Provide information about the best liquid organic fertilizer from Gamal leaves for the vegetative growth of cocoa seedlings for the community.